Pengaruh model pembelajaran Course Review Horay (CRH) terhadap hasil belajar siswa pada mata pelajaran IPS kelas IV SD Negeri 2 Dabuk Rejo - Devi Trinita; Ramanata Disurya; Mega Kusuma Putri (IKIP Siliwangi, 2026)
This study aims to determine the effect of the Course Review Horay (CRH) learning model on the learning outcomes of fourth grade students in Social Studies subjects. The background of this research is based on the low learning outcomes of students caused by the lack of variety of learning models used by teachers, so that students are less active and quickly feel bored in the learning process. The research method used is a quantitative method with a quasi-experimental Design. The Design in this study is an experimental study with a Pre-Experimental Design research Design in the form of One Group Pretest Posttest Design. The population and samples in this study were fourth grade students in one of the public elementary schools consisting of two classes, namely the experimental class using the CRH learning model and the control class using the conventional learning model. Data collection techniques were observation, test, and documentation. The instrument used was a learning outcome test given before and after treatment (pretest and posttest). The results of the instrument trial to determine the quality of a research instrument must meet the requirements, namely validity, normality, and hypothesis testing. The results of data analysis showed that there was a significant difference between the learning outcomes of students who used the CRH learning model and students who used the conventional learning model. Thus, it can be concluded that the CRH learning model has a positive effect on improving student learning outcomes in social studies subjects